Soft-Error-Immune Quadruple-Node-Upset Tolerant Latch Based on Polarity Design and Source-Isolation Technologies - Hao, Licai; Zhang, Xinyi; Dai, Chenghu; Zhao, Qiang; Lu, Wenjuan; Peng, Chunyu; Zhou, Yongliang; Lin, Zhiting; Wu, Xiulong (IEEE transactions on very large scale integration (VLSI) systems, 2024)
A soft-error-immune quadruple-node-upset tolerant latch (SEI-QNUTL) with a low delay and high performance is proposed using 65-nm CMOS technology. The proposed SEI-QNUTL design consists of three soft-error-immune static random access memory (SEI-SRAM) cells. Furthermore, each SEI-SRAM cell employs polarity design and source-isolation technology to reduce the number of sensitive nodes and enhance the reliability of the latch. Compared with state-of-the-art quadruple-node-upset (QNU) tolerant latches [including high-performance and low-cost single-event multiple-node-upsets resilient (HLMR), QNU tolerant latch (QNUTL), and Latch Design and Algorithm-based Verification Protected against Multiple-Node-Upsets (LDAVPM)], the proposed SEI-QNUTL design reduces (on average) the area, delay, and area-power-delay-product (APDP) by 47.0%, 25.0%, 46.5%, and 66.3%, respectively. Extensive variation analysis validates that the SEI-QNUTL design is less sensitive to process, voltage, and temperature (PVT) variations regarding power consumption and delay. Furthermore, Monte Carlo (MC) simulations show that the proposed latch exhibits high reliability when performing data storage. Compared with the existing latches, the SEI-QNUTL design makes a good tradeoff among delay, power, and area, and it can thus be used in safety-critical applications.